Child Neglect and Life Satisfaction among Left-behind Children in Rural China: The Roles of Self-compassion and Gratitude - Zhang, Huiping (Journal of interpersonal violence, 2022)
Child neglect is a social problem that causes great concern and affects the long-term well-being of left-behind rural Chinese children against the backdrop of their parents having to leave them in the care of others for extended periods while they have to go and work in cities. However, previous studies have disproportionally focused on the negative processes through which child neglect may influence their life satisfaction. Guided by positive psychology, this study examined the role of self-compassion and gratitude on the association between child neglect and life satisfaction. Our research questionnaire Likert survey used a sample of 1,091 left-behind children and 754 non left-behind children from Shanxi Province and Hunan Province. The results indicated that left-behind children reported a higher level of child neglect, and that child neglect was negatively associated with left-behind children?s life satisfaction through decreased self-compassion and gratitude. The implications of these findings are that policy measures and interventions that focus on increasing the self-compassion and gratitude of neglected left-behind children may have a positive effect on their life satisfaction.